Analisis LKPD Berbasis Proyek Terhadap Peningkatkan Kemamdirian dan Keaktifan Belajar Siswa Kelas V SD Negeri Pelita Jaya - Niken Nurrohmawati; Meilinda Rismawati; Nisrinda Nasywa Tsuraya; Hermawan Wahyu Setiadi (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2026)
This study analyzes project-based Student Worksheets (LKPD) in improving student independence and active learning at Pelita Jaya Elementary School. Problems found in the field indicate that the learning process is still dominated by lecture methods, resulting in relatively low student independence and engagement in learning. Therefore, this study aims to determine how project-based LKPD can improve students' ability to learn independently and participate actively during learning. This study uses a qualitative descriptive approach through observation of the learning process and analysis of student learning outcomes in the cognitive, affective, and psychomotor domains. The results show that project-based LKPD is effective in encouraging students to build understanding through direct project activities, stimulate creativity, strengthen critical thinking skills, and increase responsibility in completing tasks. In addition, students show higher motivation, independence in managing the learning process, and increased activeness in playing, solving problems, and completing projects. Overall, project-based LKPD makes a significant contribution to improving student independence and active learning in elementary school students.